G622(P) An evaluation of the impact of environmental priming on clinical performance in simulated paediatric emergencies – a randomised controlled trial. (May 2019) - McNaughten, B; Storey, L; Corkin, D; Cardwell, P; Thompson, A; Bourke, T; O'Donoghue, D
Abstract : Aims: Time delays in the delivery of emergency treatment can be detrimental to patient care. Multiple factors have been implicated as causes of such delays including the time taken to access emergency equipment. This randomised control trial aimed to evaluate the impact of environmental priming on student performance in a simulated paediatric emergency. Methods: We randomised medical and nursing students into primed or un-primed groups. The groups then undertook a standardised simulated scenario based on a child with meningococcal septicaemia. Those in the primed arm had received a tour of the sim-suite in advance of the session and had access to an online video tour. The time taken to achieve five of the six key clinical interventions outlined in the Paediatric Sepsis Six protocol were recorded. Groups from each arm were then randomly selected to undertake focus groups with a psychologist. Results: The primed students were quicker to all five key clinical interventions and significantly quicker to administration of the first fluid bolus, administration of antibiotics and seeking senior help (p<0.05). (Table 1 ). Interestingly students participating in the focus groups suggested that they did not feel that they had gained any specific advantage from being primed, perhaps displaying a degree of cognitive dissonance. Un-primed students did not feel disadvantaged by not being primed. Conclusions: This study suggests that familiarity with the clinical environment improves clinical performance. It may be possible to address this through standardising the layout of resuscitation areas, by ensuring familiarisation with key areas during local induction and through the use of in-situ simulation in clinical settings.